Lizy

\(\sqrt{21-8\sqrt{5}}-\dfrac{11}{4-\sqrt{5}}+\sqrt{1\dfrac{4}{5}}=\dfrac{-7\sqrt{5}}{5}\)

HT.Phong (9A5)
3 tháng 2 lúc 20:27

\(\sqrt{21-8\sqrt{5}}-\dfrac{11}{4-\sqrt{5}}+\sqrt{1\dfrac{4}{5}}\)

\(=\sqrt{4^2-2\cdot4\cdot\sqrt{5}+\left(\sqrt{5}\right)^2}-\dfrac{11\left(4+\sqrt{5}\right)}{\left(4-\sqrt{5}\right)\left(4+\sqrt{5}\right)}+\sqrt{\dfrac{9}{5}}\)

\(=\sqrt{\left(4-\sqrt{5}\right)^2}-\dfrac{11\left(4+\sqrt{5}\right)}{16-5}+\dfrac{3}{\sqrt{5}}\)

\(=4-\sqrt{5}-\dfrac{11\left(4+\sqrt{5}\right)}{11}+\dfrac{3}{\sqrt{5}}\)

\(=4-\sqrt{5}-4-\sqrt{5}+\dfrac{3}{\sqrt{5}}\)

\(=-2\sqrt{5}+\dfrac{3}{\sqrt{5}}\)

\(=\dfrac{-7}{\sqrt{5}}\)

\(=\dfrac{-7\sqrt{5}}{5}\left(đpcm\right)\)

Bình luận (0)

\(\sqrt{21-8\sqrt{5}}-\dfrac{11}{4-\sqrt{5}}+\sqrt{1\dfrac{4}{5}}\)

\(=\sqrt{\left(4-\sqrt{5}\right)^2}-\dfrac{11\left(4+\sqrt{5}\right)}{16-5}+\sqrt{\dfrac{9}{5}}\)

\(=4-\sqrt{5}-4-\sqrt{5}+\dfrac{3\sqrt{5}}{5}=\dfrac{3\sqrt{5}}{5}-2\sqrt{5}=-\dfrac{7}{5}\sqrt{5}\)

Bình luận (0)

Các câu hỏi tương tự
Phạm Hà Linh
Xem chi tiết
nngoc
Xem chi tiết
Kim Tuyến
Xem chi tiết
Linh Linh
Xem chi tiết
Minh harry
Xem chi tiết
Ly Ly
Xem chi tiết
Nguyễn Thị Thu Phương
Xem chi tiết
Nguyễn Đan Xuân Nghi
Xem chi tiết
Hoàng Phú Lợi
Xem chi tiết
Hoàng Phú Lợi
Xem chi tiết